Physiological Adaptive Strategies of Oil Seed Crop Ricinus communis Early Seedlings (Cotyledon vs. True Leaf) Under Salt and Alkali Stresses: From the Growth, Photosynthesis and Chlorophyll Fluorescence - Wang, Yingnan; Jie, Weiguang; Peng, Xiaoyuan; Hua, Xiaoyu; Yan, Xiufeng; Zhou, Zhiqiang; Lin, Jixiang (Frontiers in Plant Science, 2019)
Ricinus communis is an important energy crop and also considered as one of the most potential plants for salt-alkali soil improvement in Northeast of China. Early seedling stage (such as the cotyledon expansion stage) is always vulnerable but plays a vital role in plant establishment, especially under stress condition. However, little information exists concerning the function of cotyledon and the relationship between cotyledon and true leaf in the adaptation to salt stress and alkali stress of this species. Here, Ricinus communis seedlings were treated with varying (40, 80 and 120 mM) salinity (NaCl) and alkalinity (NaHCO3), growth, photosynthesis and chlorophyll fluorescence of cotyledons and true leaves were measured. The results showed that the biomass, photosynthetic parameters and qp value of both cotyledons and true leaves decreased with increasing salt-alkali stress, and the decrease in biomass, gs and Tr of true leaves were much greater than that of cotyledons. Salt-alkali stress only reduced photosynthetic pigments and ΦPSⅡ in cotyledons, but did not affect those in true leaves. Additionally, the Fv/Fm and NPQ between cotyledons and true leaves showed different trends in salinity and alkalinity. The results suggested that alkali stress could cause much more damage to the castor bean seedlings, and different physiological responses and adaptive strategies are found in cotyledons and true leaves under salt-alkali stress. This study will help us develop a better understanding of the adaptation mechanisms of cotyledon and true leaf during early seedling stage of castor bean plant, and also provide new insights into the function of cotyledon in Ricinus communis under salt-alkali stress condition.